Optimalisasi Pembelajaran Anak Melalui Sensory Class Sebagai Upaya Untuk Meningkatkan Perkembangan Anak - Nurun Ayati Khasanah; Ferilia Adiesti; Fany Rosita Dewi; Fitria Edni Wari; Erfiani Mail (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2026)
The sensory class was implemented as a play-based learning strategy that combined tactile, movement, visual, and object-manipulation stimulation to support early childhood development. This community service program aimed to optimize children's learning through sensory class and to analyze the relationship between stimulation and fine motor development among children aged 4-6 years. The activity was conducted at TK Nurul Insani Manduro through a participatory educational approach, including initial coordination, preparation of sensory media, activity demonstration, teacher mentoring, and developmental evaluation. The target group consisted of 58 children aged 4-6 years, including 30 children in Group A and 28 children in Group B, as well as their teachers. The results were evaluated using frequency distribution and Spearman rank analysis. The tabulated data showed that among children who received good stimulation, 17 of 20 children (85.0%) had age-appropriate fine motor development. In contrast, among children with low stimulation, doubtful development dominated 16 of 30 children (53.3%), while deviation was found in 6 of 8 children (75.0%). Statistical analysis showed a p-value of 0.000 and a Spearman's rank coefficient of 0.630, indicating a strong positive relationship between stimulation and fine motor development. The program also improved teachers' understanding of structured stimulation, sensory learning media, and play-based assistance. Sensory class can therefore be applied as a practical and adaptive stimulation model in preschool settings and can be strengthened through parental involvement at home